دراسة نقدية - فوز جمال (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
People who have the means and communicating information through an independent press can essentially improve the quality of their lives as the positive effect of the press. As a provider of information to the public which is conceptually divided into the process of engineering and science are expected to press away from the curb interests indepedensinya. The post-reform era of press freedom large to raise concerns that conditions can trap members of the press for not getting the industrialization especially independent press and the increasing competition between news agencies. Members of the press can fall into a pit looking for a profit business be it social or political advantage. Journalistic ethics to be important in situations like this but still raises a fundamental question about its effectiveness in warding off bad tendency of the press in this press industrialization. Ethical issues closely related to the ethical elements of what should be done to the human as well as belief systems deeply held values​. Islam is a system of values ​​put into words the conception of morality is the basis of the word akhlaqiyaat (ethics) as a systemic foundation in carrying out a mandate. Meaning relating to ethics in carrying out the mandate that can then be parsed from conception Itqan and ihsan. Until the meanings that appear strung into a benchmark of journalistic ethics from the Islamic point of view as well as a critical study of the existing concept of journalistic ethics.